Estratigrafía Sísmica de Alta Resolución en las Rías Baixas: Pontevedra y Vigo (NO España) - Vilas, Federico; Durán, R.; García-gil, SOLEDAD; García-garcía, A. (Journal of Iberian Geology, 2000)
Detailed study of high-resolution seismic reflection profiles of the Ría de Pontevedra and Vigo (NW Spain) has allowed to distinguish 7 seismic units. Seismic units Bg and Bm are interpreted as granitic and methamorphic basement rocks respectively. The other 5 seismic units correspond to the sedimentary infill of the rías. The identification of the sequences boundaries L2 and L3 allow to recognize three sedimentary sequences (S1, S2 and S3), from oldest to youngest, 217 S. García-Gil et al. Estratigrafía sísmica de alta resolución en las Rías Baixas:... that give a progressive enlargement of the rías sedimentary basin. In the most recent sequence (S3) appear acoustic blanking and/or escape features, interpreted as due to the presence of biogenic gas in the sediments of the rías.